Evaluation of the pharmacokinetics of an experimental combined form of IFNα and IFNγ for intranasal use - E. V. Kravchenko; E. V. Bezrukova; E. V. Vorobeychikov; N. V. Skvortsov (Медицинская иммунология)
Polypous rhinosinusitis is a chronic inflammatory disease of the nasal mucosa and paranasal sinuses. Recombinant interferon has antiproliferative activity and corrects the deficiency of endogenous regulatory molecules, which allows us to consider this class of immunotropic drugs as a promising component of conservative immunotherapy for polyposis rhinosinusitis. Purpose of the study: To select the optimal composition of the experimental composition of interferons and evaluate their pharmacokinetic parameters in laboratory animals.For laboratory evaluation of the effectiveness of the auxiliary components of the proposed composition in creating a local effect, Wistar rats in the amount of 30 animals were selected, to which the proposed form of the drug (IFN1) was administered once intranasally. The control group included 30 animals that were alternately administered intranasally with a similar dose of IFNα2b and IFNγ dissolved in water for injection (IFN2). Quantitative determination of interferon concentration in blood samples was carried out using the enzyme immunoassay method. To assess the dependence of changes in concentrations in the blood of animals on the time elapsed after their administration, standard pharmacokinetic models were used. Next, the integral from the initial moment of time to infinity was determined, which corresponded to the area under the pharmacokinetic curve and made it possible to calculate a number of pharmacokinetic characteristics.The following indicators were obtained: 1) Area under the pharmacokinetic curve (AUCt) ng/ml/min – IFN1 = 683.0; IFN2 = 1707.7. 2) Absorption constant (Kp) – IFN1 = 0.13096; IFN2 = 0.03836. 3) Suction constant (Kel) – IFN1 = 0.00177; IFN2 = 0.00317. 4) Clearance (Cl) ml/min – IFN1 = 129.35; IFN2 = 51.73.Based on the differences in the values of pharmacokinetic parameters (AUCt) for the IFN1 and IFN2 preparations, it can be concluded that the use of a composition based on chitosan, succinic acid and DMSO leads to a pronounced retention of interferon in the nasal mucosa, which provides a pronounced local therapeutic effect and allows for fewer systemic adverse reactions. This composition is suitable for further clinical studies of the effectiveness of immunotherapy for polyposis rhinosinusitis.